The Influence of Digital Promotion and Perceived Quality on Repeat Purchase Through Brand Awareness as an Intervening Variable (A Case Study on Glad2Glow Products on the Shopee Platform) - Moh Farid Hidayat; Nurul Azizah (International Journal of Social, Economic, and Business, 2025)
This study aims to identify the factors influencing consumers' repeat purchase behavior of Glad2Glow skincare products, particularly through the roles of digital promotion, perceived quality, and brand awareness. A quantitative approach was used with survey data collected from 150 respondents via questionnaires. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS application. The results show that digital promotion has a significant effect on brand awareness but does not directly influence repeat purchase. Meanwhile, perceived quality significantly affects both brand awareness and repeat purchase. However, brand awareness does not have a significant direct effect on repeat purchase. Interestingly, brand awareness significantly mediates the relationship between digital promotion and repeat purchase, but does not mediate the relationship between perceived quality and repeat purchase. These findings indicate that perceived quality is a key factor in encouraging repeat purchases, while digital promotion is more effective when it first builds brand awareness.